FRAMING MEDIA DALAM KAMPANYE POLITIK JOKOWI-MA'RUF AMIN PADA PILPRES 2019 DI MEDIA SEWORD.COM. - Ivan Samora Felixius (2022)
This study highlights the framing analysis carried out by the Seword.com media on the Jokowi-Ma'ruf Amin political campaign in the 2019 Presidential Election. This research is motivated by the differences in ideology or the views of the mass media in reporting an event, especially the events regarding this political topic, namely the 2019 Presidential Election (Pilpres). This study aims to find out: 1) How is the news construction of the Jokowi-Ma'ruf Amin political campaign in the 2019 Presidential election (Pemilu) in Seword.com media. 2) How is the framing of news on the presidential general election in the online Seword.com media for November 2018 to April 2019 period. This research is a qualitative descriptive study using the framing approach of the Zhongdang Pan and Gerald M. Kosicki models. The data in this study are in the form of words, sentences, or paragraphs that are in news texts on the Seword.com media in November 2018 - April 2019 in reporting on the Jokowi-Ma'ruf Amin political campaign in the 2019 Presidential Election. The data collection technique uses the listening technique, note , and documentation. The data analysis technique used the framing analysis method of the Zhongdang Pan and Gerald M. Kosicki models. The result of data analysis conducted by the researcher shows that from the 6 news stories, Jokowi is always made with a positive tone, while Prabowo is always made with a negative tone. Seword.com's attitude of neutrality and objectivity, which is open to the public, should be more balanced in the reporting of each side, even though it is full of partiality with the candidate pair number 01 Jokowi-Ma'ruf Amin, which cannot be separated from the interests of the media owners themselves. Keywords: Framing Analysis, Seword.com, 2019 Presidential Election.